Cover Image, Volume 11, Issue 1. (17th January 2017) - Ebadian, Mahmood; Sokhansanj, Shahab; Webb, Erin
Abstract : The cover image, by MAHMOOD EBADIAN et al., is based on the Modeling and Analysis Estimating the required logistical resources to support the development of a sustainable corn stover bioeconomy in the USA, DOI:10.1002/bbb.1736 . Photo Credit: Antares Group Inc. Abstract : The cover image, by MAHMOOD EBADIAN et al., is based on the Modeling and Analysis Estimating the required logistical resources to support the development of a sustainable corn stover bioeconomy in the USA, DOI:10.1002/bbb.1736 . Photo Credit: Antares Group Inc.